The Ecodharmic Significance and Liminal Experience of the Kumbh Mela - Tiwari, Gyanendra (Worldviews, 2025)
This paper discusses the grand religious pilgrimage in Prayagraj, formerly Allahabad, every twelve years, where the Ganges, Yamuna, and the mythical Sarasvati rivers converge. The study, therefore, explores the connection between dharmic ecology—an environmental consciousness deeply rooted in Indian spirituality and the concept of liminality. This transitional phase allows for transformation in the Kumbh Mela. Dharmic ecology and liminality are spiritual and metaphysical to conceptualize how Kumbh Mela changes human relationships with nature, time, and self, making it a significant ritual ecology event. Pilgrims treat nature as a corpus and spirituality and interact with the environment based on their religious orientation (Eliade 1959: 119). Kumbh Mela is a religious practice that marks harmony with the cosmic order or Ṛta, ensuring that human practices are coordinated with celestial movements to determine when this event will occur. The focal point of this ritual is the Śāhī Snāna, or royal bath, in which devotees seek not only spiritual purification but also ecological healing, as rivers represent purifiers. From this angle, divine presence within these water bodies embodies the ecodharmic perspective: seeing nature as sacred beings, not just natural resources. This religious interaction, then, underscores a ritual for ecological consciousness and means to point out the mutual interdependence between humans and nature. The liminal experience of the Kumbh Mela allows the pilgrims to transcend social identities and stand at the threshold between the mundane and the sacred (Turner 1964: 4-20). The experience of standing at that threshold forms a framework by which one can understand the journey of the pilgrimage; travel and destination become a spiritual process for the individual when going on the journey (Davidson and Gitlitz 2002: 79). The temporary city constructed on the river floodplain exemplifies the microcosm model of sustainability. This easily destructible urban space, built with a complete break-up at the end of the Kumbh Mela, embodies the impermanence of humans and speaks to the vision of being kind when inhabiting Earth. The urban design of the Kumbh Mela supports both eternal dharmic truths and contemporary earth-friendly sustainable and ecological design principles, serving as an example of a sustainable pilgrimage. At the Kumbh Mela are four royal baths. Conceptions of collective and individual rebirth, spiritual liberation—also referred to as Mokṣa—factoring in communal, ecological stewardship, explain how these baths occur at astrologically significant times and illustrate how practices worthy of spiritual merit and Dharma coexist with their honor and preservation of nature. In this study, I would argue that the ecodharmic traditions, metaphysical thought, and environmental philosophy of the Kumbh Mela embody ancient Indian wisdom appropriate for the pressing challenges contemporary ecological knowledge poses today. Over and above being a religious congregation per se, the Kumbh Mela represents a vibrant interplay of dharma with ecology, spirituality, and urban planning, encouraging pilgrims to enact sustainable practices in their daily routine and fostering an ascetic influence in behavior.